The reality of the Entrepreneurship in Palestinian IT companies - El-Sawalhy, Emad Younis (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the reality of entrepreneurship, applying on the Palestinian IT companies in the Gaza Strip. The problem of the study was formulated in the following main question: What is the reality of entrepreneurship in Palestinian IT companies? The study applied the analytical descriptive method based on primary and secondary sources of data. The study followed the analytical-descriptive method. The questionnaire was used as a main tool for collecting data from the population, which is (129) individual employees in the departments of electronic marketing in companies, where (97.7%) were retrieved. The study reveals the high level of leadership in the Palestinian information technology in the Gaza Strip. The study recommends the necessity of establishing or developing a center for entrepreneurship in companies and diversifying the sources of funding to support entrepreneurial ideas, with the need to involve entrepreneurs with entrepreneurial ideas and profits.